“Anno ab incarnatione Domini Nostri MLXVI”: A Note about Halley’s Comet in Viterbo’s Archbishop Library Collection .......... 369 - Salvatelli, Luca (Collecting Antiquities from the Middle Ages to the End of the Nineteenth Century: Proceedings of the International Conference Held on March 25-26, 2021 at the Wrocław University Institute of Art History, 2021)
Outlined Viterbo’s archbishop library’s multifaceted book collection, the aim of this paper is representing an unknown volume now located in the CeDiDo Library – a very valuable item from a historical and cultural point of view. This item provides a preliminary clue to the scientific studies in the medieval papal court developed later in thirteenth century. As matter of fact, the Liber Canonicorum’s explicit has been enriched by a detailed astronomical description about the passage of the 1066 Halley’s comet. Therefore, the focus of this paper will be on the codicological and philological manuscript’s properties and peculiarities, comparing them with Viterbo’s historical sources and other contemporary textual and iconographic ones about the comet, useful for a correct classification, dating, and inclusion in the Studium Viterbiensis’ research on speculative framework and intellectual production.